Accelerating UMKM Digital Transformation: Mentoring in Business Model Canvas (BMC) Development and Online Marketing Strategies Based on Local Platforms - Hajar, Hajar Mukaromah; Rizal, Yani; Astutik, Wahyuni Sri; Betan, Abubakar; Nuryenda, Endang Yuda (PT Inovasi Pratama Internasional, 2025)
The digital transformation of Micro, Small, and Medium Enterprises (MSMEs/UMKM) has become increasingly critical in Indonesia's post-pandemic economic recovery. This qualitative study examines the effectiveness of mentoring programs focused on Business Model Canvas (BMC) development and online marketing strategies using local platforms for UMKM acceleration. Through in-depth interviews with 15 UMKM owners, 5 mentors, and 3 platform representatives across various Indonesian cities, this research employs thematic content analysis to understand the impact of structured mentoring on digital transformation outcomes. The findings reveal that comprehensive BMC mentoring significantly enhances UMKM owners' understanding of business model components, with participants demonstrating improved capability in customer segmentation, value proposition development, and revenue stream diversification. Local platform adoption showed superior outcomes compared to international alternatives, with 35% average sales increases and enhanced operational efficiency. The study identifies key success factors including local language support, lower commission fees, and community-based learning approaches. These findings contribute to the understanding of effective community service methodologies for UMKM digital transformation and provide practical frameworks for scaling mentoring programs across Indonesia's diverse economic landscape.